Analisis Laporan Pendapatan dan Biaya Dalam Menunjang Peningkatan Laba Pada Hotel Garuda ZZ Kota Pagar Alam - suryani evroza komaria; Ayu Agustina; Deki Fujiansyah (Ekonomia, 2022)
This study aims to analyze the income and expense reports in supporting the increase in profit at the Garuda Zz Hotel, Pagar Alam City. The data collection technique used in this research is the Interview Method, Observation and Documentation. The analytical method used in analyzing the problems found is using the Quantitative Descriptive Method. As for the Fluctuating Income Indicator, where income in 2020 has decreased due to COVID-19, but in 2021 it will rise again because COVID-19 has begun to subside. while the calculation of the load using the Accrual Basis Method. To improve this, the authors suggest that Garuda Zz Hotel should maintain the Accrual Basis Method but for the calculation of income using PSAK No. 23, so that the calculation of income is more precise.